A brief intervention to increase physical activity behavior among adolescents using mental simulations and action planning - Koka, A.; Hagger, Martin (Routledge, 2017)
This study evaluated the effectiveness of a brief integrated theory-based intervention to increase physical activity (PA) among adolescents over a three-month follow-up period. A 2 (mental simulation: present vs. absent) × 2 (action planning: present vs. absent) × 4 (time: baseline vs. one-month vs. two-month vs. three-month follow-up) mixed-model randomized controlled design was adopted. Adolescents aged 14–15 years (N = 267) completed baseline psychological measures and self-reported PA followed by the relevant intervention manipulation, if appropriate, with follow-up measures collected one, two, and three months later. Results revealed no significant effects for the mental simulation and action planning strategies nor the interaction of the two strategies. However, among participants with low levels of baseline PA, participants in both mental simulation alone and action planning alone groups reported significantly higher levels of PA at one-month follow up than other groups, suggesting that individual intervention components may be effective in low-active adolescents.